Problem Statement Formulation in Computing Research: A Systematic Review and a Proposed Computing-Specific Framework - Tirivashe Mafuhure; Mampilo Phahlane; Charles Mbohwa (Journal of Applied Informatics and Computing, 2026)
The development of a well-formulated problem statement is still considered an integral but often insufficiently addressed step of the research process within computing research. Although essential for creating coherent research, selecting adequate methodology, and making scientific contributions, there is still no specific guidance on the development of computing-relevant research problem formulations, structuring, and formulation practices. This paper provides a systematic review of how the research problem is conceptualized, formulated, and operationalized in computing research. It aims to determine the common methodological problems of problem formulation, and to explore the methodological practices, recurrent strengths, weaknesses, and uniqueness of problem formulation in computing research. The systematic review was performed following the PRISMA protocol by analysing peer-reviewed journal articles published between 2014 and 2026 in major scientific databases such as IEEE Xplore, ScienceDirect, SpringerLink, and DOAJ. The search resulted in the identification of 57 papers. In turn, 16 articles met the inclusion and exclusion criteria after conducting screening, eligibility, and quality assessment. Thematic synthesis using open coding, axial coding, and theme development was utilized in order to analyse the data. Five recurring methodological weaknesses of problem statement formulation in computing research were identified are topic-problem confusion, solution orientation in early stages of problem formulation, poor empirical support, inadequate contextualization, and poor methodological alignment. Moreover, several significant discipline-specific differences in terms of problem conception were found. Some methodological approaches were detected in computing research. At the same time, their use appeared inconsistent and poorly coordinated across computing disciplines. Hence, the research proposes the Problem Statement Formulation Model (PSFM) as a structured methodological framework for problem formulation within computing research. PSFM consists of five consecutive steps that are context analysis, evidence-based gap recognition, problem structure creation, significance justification, and problem formulation. In contrast to existing generic frameworks, the presented model introduces an integrated methodology specifically adapted to the computing field. The paper concludes by discussing the findings' contribution to methodological guidance, postgraduate supervision, and training of researchers in computing disciplines.